ChemInform Abstract: Efficient Photolytic C—H Bond Functionalization of Alkylbenzene with Hypervalent Iodine(III) Reagent. Issue 28 (June 2016) - Sakamoto, Ryu; Inada, Tsubasa; Selvakumar, Sermadurai; Moteki, Shin A.; Maruoka, Keiji
Abstract: Benzyl esters are prepared by direct benzylic C—H bond esterification of alkylbenzenes by the combination of a hypervalent iodine reagent with visible light irradiation.